The shattered self : the end of natural evolution - Baldi, Pierre (MIT Press, 2001)
Scientific and technological advances now allow us to manipulate genomes directly at the level of single genes and their constituents, with a speed and precision that far exceed what natural evolution has been able to achieve over the past 3.5 billion years. We already have in vitro fertilization and animal cloning; in the future human cloning and the exploitation of embryonic stem cells, among other capabilities, may be routine. At the same time, we are developing machines that will surpass the human brain in raw computing power and building an interconnected world of information-processing devices.In this book Pierre Baldi explores what it is about these phenomena that makes us so uneasy--the shattering of the human self as we know it. Eventually we must come to terms with the fact that genomes, computations, and mind are fluid, continuous entities, in both space and time. The boundary between the self and the world has begun to dissolve and ultimately may evaporate entirely. Baldi offers not predictions but an informed exploration of our current state of knowledge and the possibilities that lie ahead.